Efficacy of Umbilical Cord Lactate Level in Predicting the Hypoxic Ischemic Encephalopathy (HIE) in Neonates After Perinatal Asphyxia - Arshad, Muhammad Bilal; Ayub, Iqra; Arshad, Bakhtawar; Hussain, Shabbir; Nadeem, Muhammad Tariq; Tabbusum, Samina (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare the umbilical artery lactate level in different grades of Hypoxic Ischemic Encephalopathy in neonates with perinatal asphyxia. Study Design: Cross-sectional study. Place and Duration of Study: Pak Emirates Military Hospital, Rawalpindi Pakistan, from Dec 2021 to Feb 2022. Methodology: A group of 70 neonates with gestational age of 36 weeks (252 days) and above, who were reported to have any late deceleration, meconium staining of liquor, low 5 minute APGAR score and need for neonatal resuscitation for more than 1 minute, were selected and their umbilical artery lactate levels were measured. Neonates were classified into two groups by using Sarnet and Sarnet classification with Group-A having neonates with No or Mild Hypoxic Ischemic Encephalopathy and Group-B with Moderate to Severe Hypoxic Ischemic Encephalopathy. Results: A total of 70 patients were enrolled in the study with median gestational age of 267 days and mean weight of 2.70±0.60 kg. A total of 45 neonates were found to have No or mild Hypoxic Ischemic Encephalopathy (Group-A) with mean lactate level of 3.64±1.49 mmol/L and 25 diagnosed with moderate to severe Hypoxic Ischemic Encephalopathy (Group-B) had mean lactate level of 9.40±2.26 mmol/L. Mean lactate levels were significantly raised for Moderate to Severe Hypoxic Ischemic Encephalopathy (p≤0.005). Conclusions: The umbilical artery lactate level can be used as a predictor of moderate-to-severe Hypoxic Ischemic Encephalopathy in neonates suffering from perinatal asphyxia.